Testicular regression syndrome: A retrospective analysis of clinical and histopathological features in 570 cases - He, Tian-Qu; Wen, Rong; Zhao, Yao-Wang; Liu, Li; Hu, Jian-Jun; Liu, Yu; Peng, Qian-Long (Frontiers in Pediatrics, 2022)
This study aimed to analyze the clinical features and pathological findings of the largest reported case series of testicular regression syndrome (TRS). Data, including age, affected side, color Doppler ultrasound results, surgical methods, intraoperative conditions, and pathological examinations, of children with unilateral TRS who were treated in our center from December 2012 to November 2021 were retrospectively analyzed. A total of 570 patients were included in this study. The mean age at surgery was 38 (5–193) months. There were 457 cases (80.2%) of left TRS. Preoperative color Doppler ultrasonography found nubbins in 172 cases (30.2%). The long diameter of the contralateral testis was 17.11 (±4.22) mm, and the volume was 0.81 (±1.15) mL. The long diameter was greater than or equal to 1.6 cm in 62.0% of the patients (240/387) aged younger than 3 years. Laparoscopy was performed as the initial surgical step in 513 cases, of which 96.7% of the children had closed internal rings. One or more lesions of fibrosis, hemosiderin, and calcification were found in 92.4% (474/513) of the excised remnants. Germ cells were present in 16 cases (3.1%). In conclusion, TRS is more common on the left side and is usually accompanied by a closed internal ring and compensatory hypertrophy of the contralateral testis. Germ cells are only present in cases where the spermatic cord enters the internal ring. We recommend further exploration and excision of the remnants in these patients, although this procedure may not be applicable in cases where only the vas deferens has entered the internal ring.